The Scientific Sanad Tradition of Islamic Boarding Schools as a Basis for Strengthening Moderate Religion in the Post-Truth Era - Muliana, Siti; Yahya, Mad; Rohmatun, Taaibah Ngaunillah (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the impact of new media on the dissemination of religious ideology, particularly in Indonesia, where the process of spreading Islam has traditionally been carried out through face-to-face meetings between students and teachers. With the rise of the internet, however, the transfer of religious knowledge has shifted to digital spaces such as websites, social media, and other online platforms. This has led to a proliferation of religious content and a blurring of the religious expert authorities, some of which may hold extremist and intolerant views. The objective of the study is to examine the major role of the pesantren educational tradition as the basis for strengthening religious moderation in the post-truth era. In the post-truth era, there are shifting models of Islamic da’wah which was originally at the practical level to the media level, as well as the rise of phenomenon where the objective facts do not influence public opinion. The researcher used a qualitative approach to identify the role and implications of the sanad tradition on the high index of potential for radicalism by internet users. Qualitative work steps such as observation, documentation, and literature study techniques were used by the author in this research. The researchers identified that Islamic boarding schools in their history are closely related to the scientific sanad tradition which can be a counter to extremist religious content in social media. The scientific sanad tradition in Islamic boarding schools has argumentatively not easily believed in religious doctrines without going through direct contact with spiritual teachers. The principle of continuous scientific sanad tradition between teachers and students, as well as direct scientific transformation, is important amid the acceptance of religious narratives circulating on social media regardless of their source and legitimacy.